COLLABORATIVE ROBOTS INTELLIGENT CONTROL USING FUZZY LOGIC WITHIN INDUSTRY (Journal of Universal Science Research, 2025)
The article presents a study of intelligent control of collaborative robots using fuzzy logic within Industry 5.0, which is aimed at ensuring safe and effective interaction between robots and a dynamic environment. The proposed mathematical models and numerical simulations demonstrated the ability of the system to successfully avoid collisions and reach target points while maintaining smoothness and optimality of trajectories. The results obtained confirm the advantages of fuzzy logic for describing uncertainty and making decisions in real time, which is critically important for the development of flexible manufacturing systems. The presented approach opens up prospects for further integration with digital twins and machine learning in order to increase the level of autonomy and adaptability of robotic systems.